Antidepressant-Like Effects of Low- and High-Molecular Weight FGF-2 on Chronic Unpredictable Mild Stress Mice - Wang, Lin; Li, Xi-Xi; Chen, Xi; Qin, Xiao-Yan; Kardami, Elissavet; Cheng, Yong (Frontiers in Molecular Neuroscience, 2018)
The occurrence of depressive disorder has long been attributed to monoamine variation, and drug therapy strategies are focused on changing the effectiveness of monoamine. However, the limited success achieved by changing these processes stimulated the search for alternative mechanisms and treatments. FGF-2, which is produced as high molecular weight (HMW) and low molecular weight (LMW) isoforms, is a potent modulator of development and maintainer of the nervous system and has been shown to play a role in numerous psychiatric disorders. In the present study, we investigated the anti-depression effects of HMW- and LMW- FGF2 against chronic stress-induced depression. Both peripheral LMW and HMW FGF-2 attenuated the depression-like symptoms in chronic unpredictable mild stress (CUMS) mice to a similar extent, as determined by the forced swim test, tail suspension test and sucrose preference test. We then showed that CUMS induced oxidative stress in the mice were inhibited by FGF-2 treatments both in central and peripheral. We also demonstrated that LMW and HMW FGF-2 activated the ERK and AKT signaling pathways to increase Bcl-2 expression and inhibit caspase-3 protein activity in CUMS mice. Interestingly, HMW FGF-2 enhanced the activity of the neurotrophic factor BDNF to a greater extent than LMW FGF-2 in the hippocampus. Taken together, the results presented herein suggest that depressive symptoms can be relieved by administering different forms of FGF-2 peripherally in a CUMS-induced depression model, by a similar anti-depression signaling pathway, therefore suggesting a potential clinical use of FGF-2 for treatment of depression.